The Effect of Work Environment on Flexible Working Hours, Employee Engagement and Employee Motivation - Setiyani, Aris; Djumarno, Djumarno; Riyanto, Setyo; Nawangsari, Lenny Ch. (International Review of Management and Marketing, 2019)
Employee engagement is one of the concentrations of the human resources department. Many programs are run to increase employee engagement value from year to year. This study aims to analyze the influence of work environment and flexible working hours on employee engagement with employee motivation as an intervening variable. The respondents of this study focus on millenials supervisor up from manufacture and service company in Java Island, Indonesia. The type of research used is quantitative with survey method. Research respondents were 110 people and the data were analyzed using SEM-AMOS (Structural Equation Model - Analysis of Moment Structures). The results show that there is an influence of work life balance and flexible working hours on employee engagement. We also used Sobel test to see that employee motivation have a function as a mediating or not in this study. According to the results, employee motivation has the effect of mediating between work environment and flexible working hours on employee engagement. Keywords: Work Environment, Flexible Working Hours, Employee Engagement, Employee Motivation, Manufacture JEL Classifications: J5, J81 DOI: https://doi.org/10.32479/irmm.8114